DEVELOPMENT OF SUSTAINABLE FEATURE ATTRIBUTES FOR URBAN GREEN SPACES USING MULTICRITERIA ANALYSIS - AHMAD, RABI’AH (2018)
The rapid urbanization process in Malaysia has forced the issue of urban green space to be importantly addressed with regards to promoting leisure opportunities, health benefits and aesthetic enjoyment of urban residents